Organ transplantation and donation from the point of view of medical students in Iran: Ethical aspects and knowledge - Abbasi, Mahmoud; Kiani, Mehrzad; Ahmadi, Mehdi; Salehi, Bahare (Cellular and Molecular Biology, 2018)
Organ transplantation is an effective process that prolongs the lives of individuals suffering from incapacitating conditions. The aim of this study was to evaluate the view point of medical students in Iran regarding ethical aspects and knowledge on organ transplantation and donation. The participants included 165 medical students from different faculties of Shahid Beheshti University of Medical Sciences, Tehran, Iran. They were assessed using a reliable questionnaire that examined their ethical aspects and knowledge regarding organ transplantation and donation. All data analyses were performed using Chi-square and analysis of variance tests with SPSS software. Results showed that main sources of respondents’ knowledge on organ transplantation and donation were TV, 51.52 % (n = 85) and Internet, 19.39 % (n = 32). 91.51% (n = 151) of the respondents understand and 8.48% (n =14) do not understand the concept of brain death. 49.69% (n = 82) of the respondents were willing to donate their organs. A brain death (72.12%; n = 119) donor was selected by respondents as the best option for organs transplantation. The respondents selected young patients (69.69%; n = 115) as the preferred recipients of an organ. There was no correlation between gender, age, educational level, marital status and attitude towards organ transplantation. From the results, there is need for an organized educational planning for medical students in ethical issue and knowledge on organ and tissue transplantation.